Social Construction and Education Values Based on the Study on Sangiran Museum - Kurniawan, Agung Budi (Humaniora: Journal of Indonesia Culture and Society, 2024)
The research analyzed the social indicators of history study and education values based on the Sangiran Museum study. Social and educational studies based on museum materials are still developing because they have potential prospects. Sangiran Museum is a popular ancient museum in Indonesia with valuable materials, but it still has future development prospects. Data were taken by applying documentation and observation methods. The observation was based on a qualitative approach to obtain and analyze the data. The observation was done by coming to the Sangiran Museum on 27 April 2024. It proposes two main findings and discussion. The first is the construction of the history indicators that consist of macro indicators of social-humanity aspects, physical collection, natural science, and history text era. The second finding concerns the academic and tourism potential of the Sangiran Museum values that are presented simultaneously. The academic value of the Sangiran Museum for historical study is excellent for its complete and valid collection. Meanwhile, the potential for future non-historical materials is in the English for Spesific Purposes (ESP) study based on the museum materials or study area. In the scope of prospects for tourism destinations, the museum needs to be enlarged for its activity on the internet, especially for promotion on various social media. Moreover, the facilities and information through the internet should also be developed, such as online museum libraries, catalogs, promotions, narratives of history speeches, etc. Official wisdom is also needed to support future development prospects.